Habermas and Rawls on an Epistemic Status of the Principles of Justice - Kędziora, Krzysztof (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2019)
The so-called debate between Jürgen Habermas and John Rawls concentrated mainly on the latter’s political liberalism. It dealt with the many aspects of Rawls’s philosophical project. In this article, I focus only on one of them, namely the epistemic or cognitivistic nature of principles of justice. The first part provides an overview of the debate, while the second part aims to show that Habermas has not misinterpreted Rawls’s position. I argue that Habermas rightly considers Rawls’s conception of justice as a moral one. In the last part, I discuss two key questions raised by Habermas. The first concerns the relation between justification and acceptance of the principles of justice. The second concerns the relation between two validity terms: truth and reasonableness.